Method for in-situ synthesis of Al2O3-TiC reinforced iron-based composite material

Through the two-step reduction of titanium concentrate in situ synthesis method, the problem of difficulty in recycling and utilization of Fe and Ti elements in titanium concentrate is solved, and the high-temperature creep resistance and controllability of Al2O3-TiC-enhanced iron-based composite materials are achieved, which is suitable for Industrial production and reduce energy consumption and CO2 emissions.

CN119243016AActive Publication Date: 2025-01-03CHONGQING UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411376388.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

In the prior art, the Fe and Ti elements in titanium concentrate are difficult to recover and utilize, resulting in complex utilization of titanium concentrate, time-consuming and high energy consumption, and poor controllability of Al2O3-TiC-enhanced iron-based composite materials in situ. Impacts material performance and industrial production.

Method used

The two-step reduction titanium concentrate in situ synthesis method is adopted. First, the titanium concentrate powder is milled and reduced-carbon nitrided under a reducing atmosphere, and then mixed with aluminum powder to grind and press, and then sintered by vacuum hot pressing and finally grinding. Polishing obtains Al2O3-TiC-enhanced iron-based composite material, controlling the atmosphere and temperature to adjust the Al2O3 content and ensuring material performance.

Benefits of technology

The simultaneous recycling and utilization of Fe and Ti in titanium concentrate is achieved, which reduces energy consumption, improves the high-temperature creep resistance and overall performance controllability of the material, is suitable for industrial production, and reduces CO2 emissions through clean energy reducing agents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243016A_ABST
    Figure CN119243016A_ABST
Patent Text Reader

Abstract

The invention discloses a method for in-situ synthesis of an Al2O3-TiC reinforced iron-based composite material. According to the method, firstly, CH4-H2 gas is used as a reducing agent, iron oxide and titanium oxide in the titanium concentrate are preliminarily reduced into metal iron and Ti (C, O) at the low temperature, then metal aluminum is used for conducting deep deoxidation reduction on the reduced titanium concentrate, and meanwhile the Al2O3-TiC reinforced iron-based composite material is synthesized in situ. According to the method, reduction of iron and preliminary carbonization of titanium in the titanium concentrate can be achieved at the low temperature through a two-step reduction method, the content of Al2O3 in the Al2O3-TiC reinforced iron-based composite material is regulated and controlled by precisely controlling the content of oxygen in a reduction product Ti (C and O), and preparation of the high-quality iron-based composite material is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metallurgy, and in particular to a method for in-situ synthesis of Al2O3-TiC reinforced iron-based composite materials by two-step reduction of titanium concentrate. Background Art

[0002] Steel is a general term for iron-carbon alloy materials. The abundant iron ore reserves and relatively low smelting costs make steel the most widely used structural material at present. It is called "industrial skeleton" and is widely used in petrochemical, metallurgical machinery, mining, aerospace, transportation and other fields. Steel itself has excellent mechanical properties, and can be improved by adding various alloy elements (such as nickel, chromium, manganese, etc.) to improve its special properties in terms of wear resistance, corrosion resistance, high temperature stability, etc. However, with the increase in production demand and the rapid development of industrial technology, cutting-edge industrial fields such as aerospace, high-speed railways, and high-performance automobiles have put forward higher requirements for the performance of materials. Traditional single steel materials can no longer meet the needs of cutting-edge industries.

[0003] Metal matrix composites are composite materials that use metal or alloy as the matrix and one or more metal or non-metallic fibers, whiskers, particles, etc. with specific properties (such as wear resistance, corrosion resistance, high temperature stability, etc.) as the reinforcement phase, and are metallurgically combined by external addition or in-situ generation. Metal matrix composites have become the preferred structural materials to replace traditional single metal materials due to their unique high specific strength and specific stiffness, wear resistance and high temperature resistance. They have attracted widespread attention from material researchers at home and abroad and have now become an important branch of the modern composite material system.

[0004] The rich raw material resources, low cost and excellent properties of steel materials make the steel-based composites prepared with them as the substrate have great application prospects. However, the current research on metal-based composites mainly uses metals or alloys such as Al, Mg, and Ti as the matrix, and the research on steel-based composites is still in its infancy. Among them, particle-reinforced steel-based composites have attracted widespread attention from researchers due to their advantages such as low cost and easy molding. The preparation methods of particle-reinforced steel-based composites are also mainly divided into external reinforcement composite method and in-situ composite method. The reinforcement phase particles are mainly oxide ceramic particles, carbide ceramic particles and nitride ceramic particles. External reinforcement composite methods such as casting composite and powder metallurgy composite often use high-purity steel materials and reinforcement phase particles as synthetic raw materials, which have problems such as complex process, high cost, and easy agglomeration of reinforcement phase particles. In contrast, the in-situ composite method has attracted increasing attention from researchers due to its relatively simplified preparation process, low material manufacturing cost, and excellent and controllable material properties. Oxide ceramic particles such as Al2O3 have high hardness, good wear resistance and good high-temperature stability. As a reinforcement phase, they can effectively improve the high-temperature creep resistance of iron-based composite materials. However, the wettability of Al2O3 particles to steel is poor. When the external reinforcement composite method is used, the Al2O3 particles are not tightly bonded to the matrix interface, which is prone to casting defects. The in-situ composite method can fundamentally solve the problem of poor wettability between oxide ceramic particles such as Al2O3 and steel substrates. Carbides such as TiC have good wettability with steel materials and have the characteristics of high hardness, wear resistance, corrosion resistance and high elastic modulus. However, the high-temperature creep resistance of carbide-reinforced iron-based composite materials is poor, which will greatly affect the application value of composite materials.

[0005] Although my country is rich in iron and steel resources, most iron ores have a low grade and a high proportion of polymetallic paragenesis. The rich vanadium-titanium magnetite resources in Panxi, Sichuan are typical polymetallic paragenesis ores, and their reserves of vanadium, titanium, iron and other resources are among the highest in the country. After multiple beneficiation processes, Panxi vanadium-titanium magnetite can obtain vanadium-titanium magnetite concentrate and titanium concentrate. The main component of titanium concentrate is FeTiO3. Since it is impossible to recycle Fe and Ti at the same time, the iron oxides in the titanium concentrate are generally reduced and separated by electric furnace smelting, and then the titanium resources are recycled. Therefore, the entire titanium concentrate utilization process is relatively complicated, time-consuming, energy-intensive, and has high carbon emissions.

[0006] In view of the difficulty in recycling Fe and Ti elements in titanium concentrate, relevant scholars have proposed to use the rich Ti and Fe resources in ilmenite to directly synthesize Al2O3-TiC dual-reinforced iron-based composite materials in situ through aluminothermic and carbon-thermal one-step reduction. This method is to add a certain proportion of aluminum powder and carbon powder to the titanium concentrate, use metal aluminum to reduce and remove oxygen in FeTiO3 at high temperature and generate Al2O3 in situ, and the reduced metal titanium combines with C to generate TiC in situ, thereby obtaining Al2O3-TiC reinforced iron-based composite materials. However, the aluminothermic reduction of FeTiO3 is a highly exothermic process, and the reaction of self-generated TiC is too intense. The interface between the in-situ generated reinforcement phase and the matrix is ​​prone to casting defects due to excessive temperature, affecting the overall performance of the composite material. At the same time, all the oxygen in FeTiO3 in titanium concentrate will react with Al to generate Al2O3, resulting in excessive content of Al2O3 generated in situ in the composite material. Relevant studies have shown that the proportion of Al2O3 in Al2O3-reinforced iron-based composite materials should be less than 10%, and excessive Al2O3 will affect the overall performance of the iron-based composite material. Therefore, the method of in-situ synthesis of Al2O3-TiC dual-reinforced iron-based composite materials by one-step reduction of titanium concentrate by aluminothermic and carbothermic methods has poor controllability, and the product quality is difficult to control, which is not suitable for large-scale industrial production. Summary of the invention

[0007] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a method for in-situ synthesis of Al2O3-TiC reinforced iron-based composite materials by two-step reduction of titanium concentrate with strong controllability and low energy consumption.

[0008] To achieve the above object, the present invention adopts the following technical solution: a method for in-situ synthesis of Al2O3-TiC reinforced iron-based composite material, comprising the following steps:

[0009] S1: Grind the titanium concentrate to obtain a powder particle raw material with a particle size of 0.1-0.2 mm, and then reduce and carbonize the powder particle raw material under a reducing atmosphere to obtain a reduction-carbonitridation product. The reduction temperature is 1100-1200°C, the reduction time is 2-3h, and the reducing atmosphere is CH4-H2-Ar. The volume proportion of each gas in the reducing atmosphere is: CH4 is 4-8%, H2 is 72-96%, and Ar is 10-20%.

[0010] S2: The aluminum powder and the reduction-carbonitridation product obtained in S1 are mixed and ball-milled to a size below 0.074 mm, and then pressed into blocks using a press.

[0011] Among them, the amount of aluminum powder added in and are the molar amounts of TiO2 and Ti(C,O) in the reduction-carbonitridation product of S1, respectively, x+y=1.

[0012] S3: The block obtained in S2 is subjected to vacuum hot pressing sintering, the sintering temperature is 1100-1200° C., the sintering time is 0.5-2 h, and the hot pressing pressure is 20-25 MPa.

[0013] S4: grinding and polishing the sintered product obtained in S3 to obtain an Al2O3-TiC reinforced iron-based composite material.

[0014] Furthermore, the titanium concentrate in S1 is first subjected to a pre-oxidation treatment to improve the reduction kinetics of the titanium concentrate. The pre-oxidation treatment is carried out at a temperature of 900-1000° C. for 3-4 hours in an air atmosphere.

[0015] Furthermore, the pressure of the pressing machine in S2 is set to 20-25 MPa, and the pressing time is 2-4 min.

[0016] Furthermore, the grinding and polishing process in S4 needs to ensure that the surface of the sintered block is bright and has no scratches visible to the naked eye.

[0017] Furthermore, in the reduction-carbonitridation product in S1, the reduction rate of iron oxide is ≥99%, and the reduction rate of titanium oxide is ≥96%.

[0018] An Al2O3-TiC reinforced iron-based composite material is prepared by the above-mentioned method for in-situ synthesis of Al2O3-TiC reinforced iron-based composite material.

[0019] Compared with the prior art, the present invention mainly has the following advantages:

[0020] 1. The traditional external reinforcement composite method cannot solve the problem of poor wetting between the oxide ceramic particle reinforcement phase and the matrix. The present invention generates the Al2O3 reinforcement phase in situ by deep deoxidation of Al powder Ti(C,O), solving the problem of poor wetting between the Al2O3 ceramic particle reinforcement phase and the matrix. At the same time, compared with a single TiC reinforced iron-based composite material, the Al2O3-TiC reinforced iron-based composite material prepared by the present invention has good high-temperature creep resistance due to the addition of Al2O3 particles.

[0021] 2. The one-step reduction in-situ synthesis method requires the use of metallic aluminum to completely reduce the iron oxides and titanium oxides in the titanium concentrate. Therefore, the number of Al2O3 reinforcing phase particles generated in situ is fixed and cannot be regulated, and excessive Al2O3 content will have an adverse effect on the performance of the iron-based composite material. The present invention generates Al2O3 reinforcing phase particles in situ by deep deoxidation and reduction of titanium concentrate reduction product Ti(C,O) by Al powder, which not only reduces the amount of Al2O3 generated, but also controls the oxygen content in Ti(C,O) by adjusting the reduction temperature, reduction time and gas composition ratio in the gas-based reduction process, thereby accurately controlling the Al2O3 content generated in situ and obtaining an iron-based composite material with superior performance.

[0022] 3. The present invention adopts a gas-based reduction method to reduce FeTiO3 in titanium concentrate to Fe and Ti(C, O). Fe and Ti(C, O) have good wettability, good interface bonding, and are evenly distributed with each other. Al2O3 generated by deep deoxidation and reduction of Ti(C, O) by Al powder is evenly distributed around the deoxidized TiC particles. Therefore, the in-situ generated Al2O3 and TiC particles can be evenly distributed in the iron matrix, which can greatly improve the overall performance of the iron-based composite material. At the same time, the entire deoxidation process is relatively slow in heat release compared to the aluminothermic reduction of FeTiO3 and the autogenous TiC reaction, which can largely avoid the influence of local reaction overheating on the microstructure of the composite material.

[0023] 4. The present invention uses titanium concentrate as the main raw material to in-situ synthesize Al2O3-TiC reinforced iron-based composite materials, which not only greatly reduces the cost of raw materials, but also realizes the simultaneous recycling of iron and titanium resources in titanium concentrate. The trace V, Cr, and Mn elements present in titanium concentrate are also favorable alloying elements that can improve the various properties of steel materials, and the impurity MgO reacts with Al2O3 during the hot pressing and sintering process to generate MgAl2O4, which is also a potential reinforcing phase material. At the same time, the present invention uses clean energy such as CH4 and H2 as a reducing agent, which is environmentally friendly and clean, has no CO2 emissions, and the tail gas can be recycled, which also reduces the use of aluminum powder in the subsequent hot pressing and sintering process, and reduces the preparation cost to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The process flow diagram of the method of the present invention is shown in FIG. DETAILED DESCRIPTION

[0025] A method for in-situ synthesis of Al2O3-TiC reinforced iron-based composite material comprises the following steps:

[0026] S1: Grind the titanium concentrate to obtain a powder raw material with a particle size of 0.1-0.15 mm, and then perform low-temperature selective reduction on the powder raw material under a reducing atmosphere to obtain a reduction-carbonitridation product. The reduction temperature is 1100-1200°C, the reduction time is 2-3h, and the reducing atmosphere is CH4-H2-Ar. The volume proportion of each gas in the reducing atmosphere is: CH4 is 4-8%, H2 is 72-96%, and Ar is 10-20%. Specifically, the reduction temperature can be 1100°C, 1110°C, 1120°C, 1130°C, 1140°C, 1150°C, 1160°C, 1170°C, 1180°C, 1190°C or 1200°C; the reduction time can be 2h, 2.2h, 2.5h, 2.6h, 2.8h or 3h; the volume fraction ratio of CH4 to H2 and Ar can be 8:82:10, 8:77:15, 8:72:20, 6:84:10, 6:79:15, 6:74:20, 4:86:10, 4:81:15 or 4:76:20.

[0027] S2: A certain proportion of aluminum powder is mixed with the reduced titanium concentrate obtained in S1 and ball-milled to less than 0.074 mm, and then pressed into blocks using a press; the amount of aluminum powder added is in and are the molar amounts of TiO2 and Ti(C,O) in the reduction-carbonitridation product of S1, respectively, x+y=1.

[0028] S3: hot pressing and sintering the block obtained in S2, the sintering temperature is 1100-1200°C, the sintering time is 0.5-2h, and the hot pressing pressure is 20-25Mpa. Specifically, the sintering temperature can be 1100°C, 1110°C, 1120°C, 1130°C, 1140°C, 1150°C, 1160°C, 1170°C, 1180°C, 1190°C or 1200°C, and the sintering time can be 0.5h, 0.8h, 1.0h, 1.2h, 1.5h, 1.8h or 2h; the hot pressing pressure can be 20Mpa, 22Mpa or 25Mpa.

[0029] S4: The sintered product obtained in S3 is ground and polished, and then Vickers hardness is tested. The hardness testing method is Vickers hardness testing, and the unit is GPa.

[0030] Specifically, the titanium concentrate in S1 will first be pre-oxidized to improve the reduction kinetics of the titanium concentrate. The pre-oxidation temperature is 900-1000°C, the time is 3-4h, and it is carried out in an air atmosphere. CH4 in the reducing gas is mainly used as a reducing agent and a carbonizing agent, H2 is mainly used to assist in reduction and inhibit the rapid cracking of CH4 at high temperatures, and Ar is used as a protective gas, which can also reduce the amount of H2. Specifically, the pre-oxidation temperature can be 900°C, 920°C, 950°C, 980°C or 1000°C, and the time can be 3h, 3.2h, 3.5h, 3.8h or 4h.

[0031] Specifically, the reduction-carbonization process in S1 is the reduction of iron oxides in titanium concentrate, the reduction rate of iron oxides in the reduction-carbonitridation product is ≥99%, the reduction rate of titanium oxides is ≥96%, and the reduction-carbonization product of titanium oxides is Ti(C, O), which is a solid solution of TiC and TiO, and TiC / TiO≥1.

[0032] Specifically, the pressure of the press in S2 is set to 20-25Mpa, and the pressing time is 2-4min; the amount of aluminum powder added is determined according to the oxygen content of the titanium-containing phase in the S1 product, and its normal addition amount is However, considering the high-temperature evaporation loss of metallic aluminum during the hot pressing sintering process and the trace amount of iron oxides remaining in the S1 reduction product, the amount of modified aluminum powder added is 1.1 times the normal amount.

[0033] Specifically, the grinding and polishing process in S4 is to use 400, 600, 800, 1000, 1500 and 2000 mesh sandpaper to grind in sequence, and then use a polishing agent to polish. Finally, the sample must be guaranteed to have no scratches visible to the naked eye.

[0034] The present invention is further described in detail below with reference to the accompanying drawings and specific examples.

[0035] Taking Panzhihua vanadium-titanium magnetite as raw material, its main chemical composition is shown in Table 1.

[0036] Table 1 Chemical composition analysis of Panzhihua titanium concentrate (pure oxide, wt.%)

[0037]

[0038] Example 1: A method for in-situ synthesis of Al2O3-TiC reinforced iron-based composite materials by two-step reduction of titanium concentrate, the specific steps are as follows:

[0039] S1: After pre-oxidation at 900℃ for 3h, the Panzhihua titanium concentrate was ground and screened to obtain a powder particle raw material with a particle size of 0.1-0.2mm. 10.0g of the sample was weighed and placed in a high-temperature tube furnace for heating. Ar was introduced during the heating process to remove the air in the furnace tube. After the temperature reached the reduction temperature, CH4-H2 gas was introduced to reduce the iron oxide and reduce the titanium oxide. After the reduction was completed, it was cooled in an argon atmosphere. The reduction temperature was 1100℃, the reduction time was 2 hours, and the volume fraction ratio of CH4 to H2 and Ar was 8:82:10.

[0040] S2: After the high-temperature tubular reactor is cooled to room temperature, the reduced titanium concentrate powder particles are taken out, and then crushed and ball-milled to less than 0.074 mm, a certain proportion of aluminum powder is added to obtain the sintering raw material of the iron-based composite material, and the mixed sintering raw material is pressed into a cylinder with a diameter of 2 cm using a press. The reduction rate of iron oxide in the titanium concentrate is 99.3%, the reduction rate of titanium oxide is 96.3%, and the chemical formula composition of the reduction product Ti(C,O) is TiC 0.61 O 0.39 ; The normal addition amount of aluminum powder is 0.474g, and the improved addition amount is 0.521g.

[0041] S3: placing the sintered raw material block in a vacuum hot pressing furnace for hot pressing sintering at a sintering temperature of 1200° C. for 2 hours.

[0042] S4: After the vacuum hot pressing furnace is cooled to room temperature, the sintered samples are taken out and the sample surfaces are polished with sandpaper and polishing paste. The Vickers hardness of the sintered product is tested to be 22.3 Gpa.

[0043] Examples 2-9 adopt the same preparation method as Example 1, the only difference is the selection of process parameters, see Table 2 for details:

[0044] Table 2

[0045]

[0046] The test results of the reduction carbonization products and hot pressing sintering products obtained in Examples 1 to 9 are shown in Table 3:

[0047] Table 3

[0048]

[0049] It can be found from Table 3 that: based on different process parameter settings, although the experimental results of the nine groups of embodiments are slightly different, they all meet the condition standards of the method of the present invention. The results of the nine groups of embodiments show that within the relevant process parameter range, the method of the present invention can accurately control the oxygen content in the titanium concentrate reduction carbide product TiCO by regulating the reducing gas composition, reduction temperature and time, thereby accurately controlling the in-situ generated Al2O3 content and obtaining the best performance iron-based composite material.

[0050] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the technical requirements of the present invention.

Claims

1. A method for in-situ synthesis of Al2O3-TiC reinforced iron-based composite materials, characterized in that: The steps include: S1: grinding and selecting titanium concentrate to obtain a powder particle raw material with a particle size of 0.1-0.2 mm, and then reducing and carbonizing the powder particle raw material in a reducing atmosphere to obtain a reduction-carbonitridation product, the reduction temperature is 1100-1200° C., the reduction time is 2-3 hours, the reducing atmosphere is CH4-H2-Ar, and the volume proportion of each gas in the reducing atmosphere is: CH4 is 4-8%, H2 is 72-96%, and Ar is 10-20%; S2: mixing aluminum powder with the reduction-carbonitridation product obtained in S1 and ball-milling the mixture to a size of less than 0.074 mm, and pressing the mixture into blocks using a sample press; Among them, the amount of aluminum powder added in and are the molar amounts of TiO2 and Ti(C,O) in the reduction-carbonitridation product of S1, respectively, x+y=1; S3: vacuum hot pressing sintering the block obtained in S2, the sintering temperature is 1100-1200°C, the sintering time is 0.5-2h, and the hot pressing pressure is 20-25Mpa; S4: grinding and polishing the sintered product obtained in S3 to obtain an Al2O3-TiC reinforced iron-based composite material.

2. The method for in-situ synthesis of Al2O3-TiC reinforced iron-based composite material according to claim 1, characterized in that: The titanium concentrate in S1 is first subjected to a pre-oxidation treatment to improve the reduction kinetics of the titanium concentrate. The pre-oxidation treatment is carried out at a temperature of 900-1000° C. for 3-4 hours in an air atmosphere.

3. The method for in-situ synthesis of Al2O3-TiC reinforced iron-based composite material according to claim 1, characterized in that: The pressure of the pressing machine in S2 is set to 20-25 MPa, and the pressing time is 2-4 min.

4. The method for in-situ synthesis of Al2O3-TiC reinforced iron-based composite material according to claim 1, characterized in that: The grinding and polishing process in S4 needs to ensure that the surface of the sintered block is bright and has no scratches visible to the naked eye.

5. The method for in-situ synthesis of Al2O3-TiC reinforced iron-based composite material according to claim 1, characterized in that: The reduction rate of iron oxide in the reduction-carbonitridation product in S1 is ≥99%, and the reduction rate of titanium oxide is ≥96%.

6. An Al2O3-TiC reinforced iron-based composite material, characterized in that: Prepared according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • In-situ hybrid particle-reinforced iron-based composite and preparation method thereof

    CN107267871A

  • TiC-Al2O3 particle reinforced steel matrix composite

    CN108103386A

  • Ceramic and metal boron nitride nanotube composites

    US20170275742A1